(untitled) (Delta Medical College Journal, 2017)
Background: The complications of pregnancy and childbirth are the leading causes of death and disability of reproductive age in developing countries. So, care of critically ill pregnant patients is an important aspect of obstetric services delivered in a tertiary care hospital. Objective: This study was conducted to find out the proportion of obstetric patients treated in ICU over a period of one year, to ascertain the frequency of serious diseases, to identify the risk factors and to determine the maternal mortality of ICU treated patients with an aim to identify the importance of a separate ICU to be incorporated within the labor and delivery suites. Materials and method: This retrospective study was conducted in Dhaka Medical College Hospital (DMCH), Dhaka, Bangladesh, during the period from January 2008 to December 2008. Total obstetric patients from all four maternity units admitted in ICU were 52 in number. Evaluation of the cases was done from records of obstetric patients treated in ICU. Necessary information was collected in a predesigned clinical sheet and the findings were compiled and necessary statistical analysis was done using SPSS. Results: ICU admission of obstetric patients in the year 2008 in DMCH was 0.82% of total deliveries and total obstetric population represented 14.3% of total ICU population. The main primary factors for ICU transfer were complications of eclampsia (59.6%) and obstetric haemorrhage (26.9%). The common final causes of ICU transfer were pulmonary oedema (35.5%) in eclamptic women and haemorrhagic shock (66.7%) in non eclamptic women. A total of 39 (75%) patients died in ICU. The major cause of death was pulmonary oedema (45.5%) in eclamptic patients and haemorrhagic shock (47.1%) in non eclamptic patients. Conclusion: Thorough evaluation of cases has revealed that many patients needed ICU treatment which could not be provided because of limited facilities. So, incorporation of a separate obstetric ICU in DMCH could be an important component of measures aimed to reduce maternal mortality rate (MMR). Delta Med Col J. Jan 2017 5(1): 15-19